Pipes and Potions: Testing the Efficacy of European Folk Preparation Methods for Anticholinergic Solanaceae Plants - Karsten Fatur; Matjaž Ravnikar; Vitjan Fras; Samo Kreft (Plants, 2022)
The present article sought to evaluate the efficiency of various folk preparation methods commonly used in Europe for employing anticholinergic Solanaceae plants. The study aimed to uncover which folk methods were effective for the extraction of the anticholinergic tropane alkaloids of these plants, atropine and scopolamine. The folk extractions that were tested sought to simulate the preparation of teas, cold-water infusions, unguents, tinctures, fortified wines, and smoking. All preparation types and a control were then put through an extraction process to see what amount of the alkaloids had been maintained. These extractions were then analysed using high-performance liquid chromatography (HPLC). Cold- and hot-water preparations, tinctures, and fortified wines all proved to be effective means of extracting atropine and scopolamine from plant material under conditions seen in folk usage. Smoking and the oil-based unguent, however, yielded no alkaloids, suggesting a lack of efficiency for these preparations, a problem with our methodology, or possible chemical changes and losses associated with the preparation procedure.